A knitted textile waveguide - Jia, X.; Tennant, A.; Langley, R. J.; Hurley, W.; Dias, T. (2014 Loughborough Antennas and Propagation Conference (LAPC), 2014)
The electromagnetic performance of a flexible knitted waveguide is examined. The waveguide is designed to operate in the X- band region and is manufactured by knitting a conducting yarn in the form of the sleeve. Measured data on transmission and return loss are presented and compared to simulated results.